2017
DOI: 10.1007/s10973-017-6232-5
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/Ni functionally graded materials (FGM) obtained by centrifugal-slip casting method

Abstract: The fabrication and the characterization of Al 2 O 3 /Ni composites with a gradient distribution of the Ni particles are reported. The composites have been obtained by centrifugal-slip casting and subsequent sintering and had the shape of a hollow cylinder. TG/DTA analysis was done for the nickel powder with the addition of the dispersant used in centrifugal-slip casting as well as for the composite green body. The measurements were performed in two atmospheres: argon and the mixture of argon and hydrogen (1:1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Citric acid (CA) (Sigma-Aldrich) and diammonium hydrocitrate (DAC) (Sigma-Aldrich) were applied as dispersants in the composite slurries. The selection of dispersant was made based on previous research [18,24,25]. Deionized Milli-Q water was used as a solvent.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Citric acid (CA) (Sigma-Aldrich) and diammonium hydrocitrate (DAC) (Sigma-Aldrich) were applied as dispersants in the composite slurries. The selection of dispersant was made based on previous research [18,24,25]. Deionized Milli-Q water was used as a solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The centrifugal slip casting (CSC) combines the effects of slip casting and centrifugation [15,[18][19][20]. The use of porous gypsum molds in the CSC method allows the removal of the liquid medium from the slurry what leads to densification of the composites.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In literature exists information about composites with molybdenum used as a metallic phase [12]. As well, Al 2 O 3 -Mo composite is described well [13]. Chmielewski et al [2] revealed experimental procedure to obtain Al 2 O 3 -Mo characterized by high density and very stable bonding between ceramic and metal phase.…”
Section: Introductionmentioning
confidence: 99%